Stylistic resource of creolization in modern mass-media - Dergach, Dmytro (Current issues of Ukrainian linguistics: theory and practice, 2018)
he author analyzes stylistic resource and potential of creolization in modern mass media. Approaches to the scientific interpretation of the phenomenon in the paradigm of communicative linguistics, functional stylistics are considered. The intra- and extralinguistic factors that actualize the means of creolization in modern media-media communication are taken into consideration. The author proposes to interpret partial and associative types of media creolization, which determine the dominant verbal / nonverbal components in media texts. The functional potential of means of creolization of the media language, aimed at informing, analyzing and influencing the language consciousness of the mass audience is also determined.
Keywords: creolization, mass media style, stylistic resource, semantic field.